Prevalence of workplace-related violence among otorhinolaryngology residents in Riyadh, Saudi Arabia - Ahmed Saleh Alsaleh; Abdulrahman Ibrahim Almotairi; Bader Mohammed Alim; Ahmad Salman Alroqi (Wolters Kluwer Medknow Publications, 2021)
Background: Violence is one of the prevalent public health concerns that healthcare staff face; a serious problem needs to be focused. Objective: The objective of the study is to estimate the prevalence of workplace-related violence among ear, nose, and throat (ENT) residents in Riyadh, capital of the Kingdom of Saudi Arabia, and to identify the common types, perpetrators, and precipitating risk factors of workplace violence (WPV). Design: This was a cross-sectional, self-administered questionnaire study. Settings: The study was conducted at King Saud University Medical City. Subjects: The study subjects were Riyadh's ENT residents. Intervention: All Riyadh's ENT residents were invited to participate in the survey in which 80 out of 90 residents participated. Our questionnaire included two domains: one includes demographic data and other includes occupational characteristics and some details related to violence. Main Outcome Measures: (1) Prevalence of WPV among Riyadh's ENT residents. (2) Identification of types and risk factors of WPV. Results: More than half of our sample had been through a violent experience before, with 60% experiencing it at least once. Most of the violent experiences were with the adult age group of 25-55 years. Male and companions of the patients were found to the most common offenders, and the most leading factors for violence are misunderstanding and miscommunication being at the top of the list at 20%. Conclusion: As more than half of the sample has experienced violence, hence, this issues needs to be focused on through different ways, including improving resident's communication skills and improving the reporting system for violent behaviors.